2012
DOI: 10.7448/ias.15.6.18093
|View full text |Cite
|
Sign up to set email alerts
|

The role of SEAD project intervention in viral suppression of HIV/AIDS patients with follow‐up and adherence barriers

Abstract: Purpose of studyIrregular FUP/ADH were associated with virologic failure [1] leading to an increase in mortality [2]. SEAD was a multidimensional intervention project, designed from the patient's perspective, to specifically attend patients with poor FUP/ ADH in an HIV/AIDS outpatient clinic.MethodsFrom Jan 2006 to May 2010, patients with poor FUP/ADH were offered SEAD inclusion, all were evaluated by a nurse or a psychologist (adherence collaborators) who assessed all the reasons and barriers precluding a cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Based on the findings and other available data appropriate measures must be taken to rectify the challenges in achieving goals of HIV/AIDS treatment, many of these issues are linked to poor adherence & follow up, lack of awareness and counselling about side effects etc. It has been shown that such interventions has resulted in higher virological suppression in patients with severe follow‐up and adherence barriers [Elıas Casado et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the findings and other available data appropriate measures must be taken to rectify the challenges in achieving goals of HIV/AIDS treatment, many of these issues are linked to poor adherence & follow up, lack of awareness and counselling about side effects etc. It has been shown that such interventions has resulted in higher virological suppression in patients with severe follow‐up and adherence barriers [Elıas Casado et al, ].…”
Section: Resultsmentioning
confidence: 99%